2007
DOI: 10.1007/s10552-007-9038-0
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of animal foods and endometrial cancer risk: a systematic literature review and meta-analysis

Abstract: This paper summarizes and quantifies the current evidence relating dietary intake of animal products and endometrial cancer. Literature searches were conducted to identify peer-reviewed manuscripts published up to December 2006. Twenty-two manuscripts from three cohort studies and 16 casecontrol studies were identified. One of these cohort studies evaluated only fried meat and another only milk consumption; they were not included in our meta-analyses. The third cohort study identified did not present exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 41 publications
3
66
1
Order By: Relevance
“…Interpretation of the evidence may not represent the views of WCRF and may differ from those in the upcoming 2007 WCRF/AICR report summarizing evidence related to food, nutrition, physical activity, and cancer risk. Exposure terms and methods can be found in the appendix of another manuscript (Bandera et al, 2007a …”
Section: Methodsmentioning
confidence: 99%
“…Interpretation of the evidence may not represent the views of WCRF and may differ from those in the upcoming 2007 WCRF/AICR report summarizing evidence related to food, nutrition, physical activity, and cancer risk. Exposure terms and methods can be found in the appendix of another manuscript (Bandera et al, 2007a …”
Section: Methodsmentioning
confidence: 99%
“…Dairy products in general and milk in particular, have also been examined in relation to cancer risk. Among women, consumption of milk may decrease risk of colorectal cancer (1) and cervical cancer (2), but have no effect on breast cancer e.g., (3)-4) or endometrial cancer (4). Results for lung cancer are quite mixed, with some studies suggesting risk reduction e.g., (5) or risk enhancement e.g., (6) that may vary by gender (7) or the histology of the tumor (8).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the highest sources of cholesterol among food groups in our questionnaire were, as expected, red meat (including higher fat beef, veal and pork), eggs, poultry and high-fat dairy. Hence, the increased risk with cholesterol may also reflect intake of animal foods that also increase EC risk (47) . Numerous observational studies have reported on the influence of dietary micronutrients in EC aetiology (5,6,20,21,(23)(24)(25)(26)28,30,31,34,(48)(49)(50)(51)(52)(53) ; two were cohort studies (6,48) and the rest were case-control studies.…”
Section: Discussionmentioning
confidence: 99%